2021
DOI: 10.1007/s11065-021-09488-2
|View full text |Cite
|
Sign up to set email alerts
|

Social Cognition in Paediatric Traumatic Brain Injury: A Systematic Review and Meta-analysis

Abstract: Background: Recent evidence suggests social cognitive deficits may be among the most profound and disabling consequences of childhood traumatic brain injury (TBI); however, it is only over the last decade that this area has received increasing research attention.Aim: This study aims to systematically review all studies reporting on the effects of childhood TBI on social cognition. Meta-analytic techniques were employed to determine the magnitude of social cognitive deficits in childhood TBI.Methods: Literature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…It comprises numerous brain regions vulnerable to the diffuse axonal injury characteristic of TBI, for example, aspects of the prefrontal cortex, temporo-parietal junction, insula, and amygdala (Adolphs, 2001 , 2003 ). TBI during childhood has the potential to derail the maturation of this network resulting in social dysfunction (Anderson, Spencer-Smith, & Wood, 2011 ; Zhi, Ryan, Konjarski, Catroppa, & Stargatt, 2021 ).…”
mentioning
confidence: 99%
“…It comprises numerous brain regions vulnerable to the diffuse axonal injury characteristic of TBI, for example, aspects of the prefrontal cortex, temporo-parietal junction, insula, and amygdala (Adolphs, 2001 , 2003 ). TBI during childhood has the potential to derail the maturation of this network resulting in social dysfunction (Anderson, Spencer-Smith, & Wood, 2011 ; Zhi, Ryan, Konjarski, Catroppa, & Stargatt, 2021 ).…”
mentioning
confidence: 99%
“…This does not fit well with a previous study implication emotion recognition as possible mechanism for problematic behavior in TBI patients (Jorna et al, 2021) nor with a recent meta‐analysis which showed higher levels of alexithymia (measured with the TAS‐20) in TBI patients (Fynn et al, 2021). Nevertheless, another recent review and meta‐analysis indicates that basic social skills (including emotion recognition) are generally intact in children and adolescents with TBI, but more complicated processes (including theory of mind and pragmatic language) were significantly impaired (On et al, 2022). This would indicate that future studies on the association between TBI and aggression should also assess higher order aspects of social cognition.…”
Section: Discussionmentioning
confidence: 99%
“…Of our identified studies, all were conducted since [ 26 ] initially completed their systematic review on the social functioning of children and adolescents following TBI that spanned studies from 1989 to 2011. More recently, a systematic review and meta-analysis surrounding social cognitive outcomes in a pediatric TBI sample was conducted by On and colleagues [ 27 ]. The following results aim to build on those works and expand those findings to include acquired brain injury more broadly, as well as other social constructs beyond social cognition alone.…”
Section: Social Outcomes In Youth Following Abimentioning
confidence: 99%
“…Social cognitive impairments have frequently been documented in youth following TBI [ 44 ], and to a lesser extent in children with ABI, such as stroke or neurological infection; however, this has been observed clinically. A recent systematic review and meta-analysis regarding social cognitive functioning in pediatric TBI patients [ 27 ] found that many youths who experience TBI are vulnerable to declines in higher-order social cognitive abilities such as pragmatic language, social problem solving, and ToM. Social information processing also involves leveraging broader executive functioning skills that are often impacted by ABI.…”
Section: Social Outcomes In Youth Following Abimentioning
confidence: 99%
See 1 more Smart Citation